2006
DOI: 10.1055/s-2006-923949
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic Clinical Course and Early White Matter Abnormalities may be Indicators of Neurological Sequelae after Status Epilepticus in Children

Abstract: Clinical course and serial neuroimaging findings are not fully described in children who have had neurological sequelae following status epilepticus. We found four patients who had neurological sequelae out of 42 children with status epilepticus in 2004. MRI studies were reviewed with specific attention to diffusion-weighted images (DWI) and the apparent diffusion coefficient (ADC). Proinflammatory cytokines, including tumor necrosis factor-alpha and interleukin-6, were measured in the cerebrospinal fluid (CSF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…In this study, central-sparing lesions were not observed in any patient within the first 3 days after onset, consistent with several previous reports. 3,[12][13][14]17 In contrast, frontal occipital lesions were recognized within the first 3 days after onset and were followed by diffuse lesions. Second, the distribution of brain lesions is different in the 2 situations.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In this study, central-sparing lesions were not observed in any patient within the first 3 days after onset, consistent with several previous reports. 3,[12][13][14]17 In contrast, frontal occipital lesions were recognized within the first 3 days after onset and were followed by diffuse lesions. Second, the distribution of brain lesions is different in the 2 situations.…”
Section: Discussionmentioning
confidence: 97%
“…3 Several studies on acute encephalopathy have also reported a biphasic clinical course. [11][12][13][14] Onset is often marked by a prolonged seizure followed by improved consciousness. However, clustered seizures, signs of frontal lobe dysfunction, and worsening of consciousness become apparent at 3-4 days after onset.…”
Section: Discussionmentioning
confidence: 99%
“…Sakuma et al showed an elevation of CXCL1, CXCL9, CXCL10, IL‐6, and IL‐8 in the CSF of 14 patients with FIRES, compared to other inflammatory neurological diseases, and showed a correlation of chemokines with a poor prognosis. The literature on FRD (AESD and HHE) is scarce; elevation of IL‐6 was reported in the CSF in case reports with AESD …”
Section: Discussionmentioning
confidence: 99%
“…AEIMSE subtypes such as hemorrhagic shock and encephalopathy syndrome (HSES), acute necrotizing encephalopathy (ANE), acute encephalopathy with biphasic seizures and late reduced diffusion (AESD), and clinically mild encephalitis/encephalopathy with a reversible splenial lesion (MERS) were classified according to previous reports [5,7]. Idiopathic hemiconvulsionhemiplegia syndrome, characterized by long-lasting febrile seizures followed by hemiplegia, has clinical and imaging similarities to AESD [2,3,8]; therefore, it was included in the AESD category as well.…”
Section: Assessmentmentioning
confidence: 99%